Review of analytical figures of merit of sensors and biosensors in clinical applications - Justino, Celine I. L. (2020)
Although the development of clinical sensors and biosensors has increased in recent years, improvements in sensitivity, selectivity, limits of detection, fast response and miniaturization are yet to be attained. Health care appears to provide the best opportunity for sensor development. Among the wide range of different sensors and biosensors, electrochemical biosensors are the most common in the clinical field, due to their high sensitivity and selectivity, portability, rapid response time and low cost. This article provides an up-to-date overview of the analytical performance of sensors and biosensors in clinical applications by discussing recent improvements, particularly due to the impact of nanotechnology.